A Shift in Storytelling: Over the Garden Wall as a Literary Reconstruction of Dante’s Divine Comedy - Manuel Botero Camacho; Guillermo Alonso Menchero (Comunicación, 2022)
Literature remains a field that serves TV creators and critics as a model both for influence and comparison. The continuity claimed by Thomas Doherty between the most recent TV narrative form with the serialised novels of Dickens or Wharton is not limited to the form itself but to its content as well. Such is the case of the TV  miniseries Over the Garden Wall, created by Patrick McHale in 2014, whose combination of Victorian fairy-tale imagery and aesthetics,as well as its reliance on literary allusion incarnates this paradigm. Within its narrative there can be found an array of literary references that range from the classics to children’s fables, as well as allusions to history and to different mythologies; an intertextual character that is featured in TV as much as in literary texts from all eras, binding the two forms together. Among the numerous texts referenced in this tale of tales, however, there is one that stands out: Dante Alighieri’s Divine Comedy.This article scrutinises suchrelationship. The main claim is that by doing so, the show highlights how Campbell’s narrative paradigm, applicable to forms of media other than literature, evinces the narrative continuity, which exists between TV and the written text.